Education About Artificial Intelligence Technology for Prediction and Early Detection of Catastrophic Disease Emergencies for Medical Personnel - Suryani, Suryani (JURNAL PENGMAS KESTRA (JPK), 2024)
Catastrophic diseases, such as stroke, heart attack, and acute respiratory failure, are medical conditions that require immediate detection and treatment to reduce the risk of death and long-term complications. However, the limited number of medical personnel in recognizing early signs and delays in the diagnosis process are major challenges in handling these diseases. The development of Artificial Intelligence (AI) technology offers innovative solutions to support medical personnel through a prediction and early detection system based on clinical data. This community service program aims to provide education to medical personnel regarding the use of AI in detecting catastrophic disease emergencies. The methods used include seminars, interactive training, and simulations of the use of AI-based software in patient data analysis. Evaluation was carried out by measuring the increase in participants' understanding and skills before and after training using questionnaires and case studies based on clinical scenarios. The results of this activity showed that medical personnel's understanding of AI increased significantly, with the majority of participants being able to interpret the results of AI predictions and integrate them into the clinical decision-making process. These findings indicate that education about AI can be a strategic step in increasing the effectiveness of handling catastrophic diseases in health facilities.